Uczenie się przedsiębiorstw w warunkach umiędzynarodowienia - Olszewska, Barbara (Organizational learning in conditions of internationalization, 2006)
The processes of internationalization and globalization have caused an increased turbulence of environment. FDI creates the needs and possibilities of organizational learning. Polish firms are affected by these processes both in direct and indirect way. This article describes some conditions of successful organizational learning created by FDI.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 132-142